Mechanical properties of concrete containing 5% and 10% of batik production waste - Mohd Syazwan, Ramli (2010)
Concrete is a man-made materials in use since the 16th century ago. Until now almost all of the main building structure in the world is made of concrete. Concrete is a material that consisting of cements, aggregates, sand and water which can be a structure that becomes stronger in terms of compression pressure and durability at a time. Many research has been done to produce concrete that is affordable, high quality and profitable. The environmental regulation have initiated in increasing interest in using waste disposal as a construction materials partially replacing the water in concrete with wastewater from industries. In this study, the idea of using waste product that is batik production waste as replacement by weight for normal water. The objective of this study concentrates on mechanical properties that are compressive and flexural strength of concrete with batik production waste. There are two different percentages in using batik production waste which are 5% and 10% that ware used to replace the normal water by weight and was tested at 7 and 28 days of ages. The strength of normal concrete play as a control mix which has been compared with the concrete containing batik production waste. The result revealed that the concrete containing 5% of batik production waste present the highest compressive and flexural strength and followed by normal concrete and concrete with 10% of batik production waste. As a conclusion, 5% of batik production waste is the optimum percentage for replacing the normal water by weight according to increase value of compressive and flexural strength.